Formulation of Supplemented Thai Custard Spread Using Jackfruit Rag and Sugar Replacement with Stevia - Panjit Pomasa; Samart Sai-Ut; Sirima Sinthusamran; Chairat Techavuthiporn (My University, 2024)
The aims of this study were to investigate whether jackfruit rags could be incorporated into a food product like custard spread, and to evaluate the sensory and physicochemical properties of the resulting products. The first trial comprised four treatments, each of which contained a different concentration of jackfruit rag (0, 20, 40, and 60% w/w). It was found that 40% jackfruit rag substitution gave higher acceptance ratings (appearance, colour, taste, odour, spreadability and overall likeness) than other concentrations. Subsequently, stevia substitution at 20% produced considerably greater sensory acceptability across all treatments. In addition, the nutritional and physicochemical characteristics of jackfruit rag-supplemented custard with 0% and 20% stevia were evaluated. Proximate analysis results showed there were no differences no difference between custard spreads fortified with 0% and 20% stevia. However, carbohydrate and energy were reduced about twice in the 20% stevia treatment. Moreover, texture profile analysis revealed that replacement with stevia increased spreadability and decreased stickiness. The results suggested that jackfruit rag could be used in custard spreads and could enhance the recovery of food waste for food production.
Keywords: Stevia; Custard-apple; Advances in Cucurbitaceae Research